Use of health services in the last year of life and cause of death in people with intellectual disability: A retrospective matched cohort study - Brameld, Kate; Spilsbury, Katrina; Rosenwax, L.; Leonard, H.; Semmens, James (BM J Group, 2018)
Objective: To describe the cause of death together with emergency department presentations and hospital admissions in the last year of life of people with intellectual disability. Method: A retrospective matched cohort study using de-identified linked data of people aged 20 years or over, with and without intellectual disability who died during 2009 to 2013 in Western Australia. Emergency department presentations and hospital admissions in the last year of life of people with intellectual disability are described along with cause of death. Results: Of the 63 508 deaths in Western Australia from 2009 to 2013, there were 591 (0.93%) decedents with a history of intellectual disability. Decedents with intellectual disability tended to be younger, lived in areas of more social disadvantage, did not have a partner and were Australian born compared with all other decedents. A matched comparison cohort of decedents without intellectual disability (n=29 713) was identified from the general population to improve covariate balance. Decedents with intellectual disability attended emergency departments more frequently than the matched cohort (mean visits 3.2 vs 2.5) and on average were admitted to hospital less frequently (mean admissions 4.1 vs 6.1), but once admitted stayed longer (average length of stay 5.2 days vs 4.3 days). People with intellectual disability had increased odds of presentation, admission or death from conditions that have been defined as ambulatory care sensitive and are potentially preventable. These included vaccine-preventable respiratory disease, asthma, cellulitis and convulsions and epilepsy. Conclusion: People with intellectual disability were more likely to experience potentially preventable conditions at the end of their lives. This indicates a need for further improvements in access, quality and coordination of healthcare to provide optimal health for this group.